RS-GIS based morphometrical and geological multi-criteria approach to the landslide susceptibility mapping in Gish River Basin, West Bengal, India. Issue 3 (1st February 2019) - Basu, Tirthankar; Pal, Swades
Highlights: The study is carried out by using 16 morphometric parameters, geology and lineaments. Drainage diversity and Relief diversity maps are prepared and integrated to get the LSZ. 7.61% area of total basin area is found highly susceptible for landslide. Abstract: Darjeeling Himalaya is one of the several mountainous areas of India which is often suffered from landslide hazards. In this paper, a multi criteria evaluation is applied using 16 morphometric indicators, geology and lineaments to identify the areas vulnerable in respect to drainage and relief conditions. As both drainage and relief parameters exert strong influences on landslide intensity, both the diversity maps are integrated for final landslide susceptibility mapping. The obtained results show that 20.17 sq. km (7.61%) area within the basin is highly susceptible for landslides, where average drainage density is 3.78 km/sq. km, relative relief is greater than 408 m and slope is greater than 12°. The validation result shows that very high landslide susceptible zone is associated with very high frequency of landslide occurrence. Beside this, ROC curve also suggests good predicted rate (86.60%) for the model. So, the proposed method can be applied for predicting landslide susceptible zone.